2022
DOI: 10.1111/emre.12541
|View full text |Cite
|
Sign up to set email alerts
|

Justice in supply chain relationships: A comprehensive review and future research directions

Abstract: This paper aims to assess the current status of research on inter‐organisational justice in supply chain relationships (SCRs), analyse its key themes and develop future research directions to advance the knowledge of SCRs. The study employed a rigorous review methodology that combined systematic and snowballing searches. In total, 98 papers published in peer‐reviewed journals between 1983 and 2020 were identified and have been descriptively and thematically analysed. Through synthesising and integrating the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 143 publications
0
4
1
Order By: Relevance
“…This result is inconsistent with previous research that revealed a positive association between distributive justice and OCB [19,35]. Specifically, equity theory predicts that employees will feel a sense of fairness when they perceive equal input-outcome ratios compared to those of others [30]. Employees with higher levels of distributive justice are likelier to exhibit OCB to improve their organizational sustainability than those with lower levels of distributive justice [19,35].…”
Section: Theoretical Implicationscontrasting
confidence: 79%
See 2 more Smart Citations
“…This result is inconsistent with previous research that revealed a positive association between distributive justice and OCB [19,35]. Specifically, equity theory predicts that employees will feel a sense of fairness when they perceive equal input-outcome ratios compared to those of others [30]. Employees with higher levels of distributive justice are likelier to exhibit OCB to improve their organizational sustainability than those with lower levels of distributive justice [19,35].…”
Section: Theoretical Implicationscontrasting
confidence: 79%
“…According to equity theory [29], employees psychologically compare the ratios of their inputs (e.g., work effort and education) and outcomes (e.g., pay and benefits) to the perceived ratios of referent others. Specifically, they feel a sense of equity (distributive justice) when they perceive that their outcome-to-input ratio is proportionally matched to that of the referent party [30]. Conversely, employees feel that the organization has treated them unfairly in terms of outcome allocation when their ratio is perceived to be either smaller than the negative equity or larger than the positive equity of the referent party [29,30].…”
Section: Distributive Justice Goal Clarity and Ocbmentioning
confidence: 99%
See 1 more Smart Citation
“…The rewardsrights trade-off cascade describes social compliance decoupling that successively transfers along a chain of two or more supply chain actors due to their simultaneous prioritization of economic outcomes over the preservation of supplier workers' rights. Most commonly, we find evidence of buyers pressuring suppliers with low price and short lead time demands while downplaying labour code compliance, which in turn drives suppliers to minimize labour costs and use work practices that speed up production in violation of labour code criteria, thus prioritizing business demands while only symbolically complying with the code criteria (e.g., Alghababsheh & Gallear, 2021;Kuruvilla et al, 2020;Lim & Phillips, 2008;Ruwanpura & Wrigley, 2011;. As an example of the rewards-rights trade-off cascade within the buyer-supplier dyad, found that suppliers responded to buyers' demands for price minimization by using less costly underage labour, paying workers below minimum wage and eliminating worker welfare and social security costs.…”
Section: Types Of Social Compliance Decoupling Cascades In Global Sup...mentioning
confidence: 99%
“…Compliance/CSR functions within buyers are often siloed and demoted in relation to purchasing functions, lacking sufficient staff and funding to allocate towards conducting frequent, comprehensive inspections of suppliers that can enable shared discovery and remediation of the root causes of non-compliance (e.g., Lindholm et al, 2016;Winstanley et al, 2002). This limits suppliers' knowledge to implement the code provisions (e.g., Alghababsheh & Gallear, 2021;Frenkel & Scott, 2002;. Along with further contraction of financial resources due to buyers' pressures to reduce product prices, this results in an inability by suppliers to comply, other than symbolically or deceptively (e.g., Locke et al, 2007aLocke et al, , 2007b.…”
Section: Cascade Type Cascading Mechanism and Shared Root Cause Among...mentioning
confidence: 99%